ACTIVITY AND SELECTIVITY OF Mo-Co/USY CATALYST ON THE HYDRODEOXYGENATION (HDO) REACTION OF ANISOLE - Khoirina Dwi Nugrahaningtyas; Yuniawan Hidayat; Prima Susan Prayekti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
This research was conducted to study the effect of the catalyst Mo-Co/USY againts product distribution and product conversion, and the effect of addition Co metals towards selectivity-products benzene on the anisole HDO. The anisole HDO was prepared by fl ow reactor. The products were analyzed by GC-MS. The main products of the anisole HDO i.e benzene and toluene. The activity with Mo-Co/USY catalyst higher than USY and termal. Mo-Co/USY B catalyst has highest selectivity-products benzene (15%).